The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s12034-008-0126-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of natural fibre reinforced polymer composites

Abstract: During the last few years, natural fibres have received much more attention than ever before from the research community all over the world. These natural fibres offer a number of advantages over traditional synthetic fibres. In the present communication, a study on the synthesis and mechanical properties of new series of green composites involving Hibiscus sabdariffa fibre as a reinforcing material in urea-formaldehyde (UF) resin based polymer matrix has been reported. Static mechanical properties of randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(127 citation statements)
references
References 24 publications
6
120
0
1
Order By: Relevance
“…A review of the has literature revealed that very little work has been done on the effective utilization of Hibiscus sabdariffa fibers as reinforcing material in polymer composites [5][6][7][8][9][10]. In the present work, therefore, we have reported some of our investigations on mechanical, morphological, thermal, and swelling behaviors of Hibiscus sabdariffa fiber-reinforced resorcinol-formaldehyde polymer matrix-based composites.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A review of the has literature revealed that very little work has been done on the effective utilization of Hibiscus sabdariffa fibers as reinforcing material in polymer composites [5][6][7][8][9][10]. In the present work, therefore, we have reported some of our investigations on mechanical, morphological, thermal, and swelling behaviors of Hibiscus sabdariffa fiber-reinforced resorcinol-formaldehyde polymer matrix-based composites.…”
Section: Introductionmentioning
confidence: 93%
“…Due to the wide variety of polymer matrices and reinforcement materials available, the design possibilities for the fabrication of polymer composites are unlimited [5][6][7]. Natural fiber reinforced composites have considerable potential to replace conventional materials like metal in structural and nonstructural applications, especially in the furniture industry [8][9][10][11]. The matrix, often a polymeric material, surrounds the reinforcement and keeps it in place.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements were made at ambient conditions. The mechanical behavior of composites was greatly affected by the distribution and orientation of the reinforcing fibers, uniformity of lignocellulosic material spread in a polymeric matrix, the interface region, the nature of the fiber matrix interface, and the distribution and orientation of the reinforcing fibers (Singha and Thakur 2008). The interfaces played an important role in the physical and mechanical properties of natural fiber reinforced polymer matrix composites.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…For instance, it has been used for reinforcement in urea formaldehyde resin-based composite which also suggested that Hibiscus sabdariffa fibre has immense scope in the fabrication of natural fibre reinforced polymer composites for vast number of industrial applications (Singha and Thakur 2008a). The graft copolymerization of Hibiscus sabdariffa also have been found to be more moisture resistant and also showed better chemical and thermal resistance ).…”
Section: Hibiscus Sabdariffamentioning
confidence: 99%